Fundamentals of using Geographical Information Systems in predicting the distribution of Helicoverpa armigera (Lepidoptera: Noctuidae) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ruzmetrov R, Abdullaev I, Gandjaeva L, Matyakubov Z, Iskandarov A, Otaev O, Ibragimov S. 2022. Fundamentals of using Geographical Information Systems in predicting the distribution of Helicoverpa armigera (Lepidoptera: Noctuidae). Biodiversitas 23: 3251-3256. This study aims to explore new ways to identify agroecological conditions that help in the occurrence of Helicoverpa armigera in cotton fields. Geographical data on soil salinity, mechanical composition, groundwater level, salinity, density of canals and drains, field Normalized Difference Vegetation Index (NDVI) coefficient of the field Helicoverpa armigera with the number of eggs regression was analyzed. The data were collected from the database of the GIS laboratory of the KRASS (Khorezm Rural Advisory Support Service) agro-consulting center, which was established with support from ZEF (The Center for Development Research) University of Bonn, Germany, and lancet satellite data in the calculation of NDVI. Data were analyzed with ArcGIS and R program. Occurrence of Helicoverpa armigera in cotton fields was found to be associated with high relative humidity and high stem length. Using the relative humidity of the air in the field and other agroecological factors, it was found that the probability of remote distribution of cotton bollworm is more than 50%.
Keywords: cotton bollworm, forecasting methods, temperature, atmospheric humidity, groundwater, NDVI, diffusion analysis.